The Correlation of P16 Expression with Degree of Differentiation and Tumor Stage in Cervical Squamous Cell Carcinoma (CSCC) - Sari, Nova Fenita; Nizar, RZ; Asri, Aswiyanti (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2023)
Background Cervical squamous cell carcinoma (CSCC) represents 70-80% of all cervical cancer cases. This cancer ranks 4th most common death cause due to malignancy in women. Cervical SCC patients were found at an older age and were detected at an advanced stage. High risk human papillomavirus (HPV) infection is main cause of SCC. Protein cyclin-dependent kinase inhibitor 2A also called p16 is a well-known tumor suppressor protein involved in cell cycle regulation, senescence, apoptosis, cell invasion and angiogenesis. This p16 protein can be used as surrogate marker for HPV infection. From several previous studies, there were differences between p16 expression relationship with differentiation degree and cervical SCC tumor stage results. Relationship research between p16 expression and differentiation degree and tumor stage of cervical SCC patients has never been conducted in West Sumatra. Methods This research was retrospective observational cross-sectional study with 35 cervical SCC cases that have been diagnosed at Anatomical Pathology Laboratory, RSUP Dr. M. Djamil Padang period January 2018-December 2019. Samples were obtained by simple random sampling from paraffin blocks derived from tumor tissue. The histopathological slide was reassessed to assess differentiation degree and tumor stage data were obtained from the patient's medical record. p16 expression in tumor cells was seen by immunohistochemical examination. To determine the correlation, bivariate statistical analysis was performed using the chi-square test with significance p<0.05 level. Results p16 high expression was found in 22 cases, tended to be higher in degree of well differentiation (40.9%) and moderate differentiation (50.0%) and was higher at an advanced stage (90.9%). Statistically, there is no correlation between p16 expression and differentiation degree with p value=0.138. There was no correlation between p16 expression and tumor stage with p value=0.337. Conclusions This study concluded that p16 expression was not associated with differentiation degree and tumor stage in cervical SCC.